Construction of a multifactor barrier evaluation system and classification of barrier types for arable land on the northern Huang-Huai-Hai Plain - Guo, Xiangyun; Zhang, Chi; Liu, Zihao; Yin, Baozhong; Wang, Hong; Li, Xuguang; Zhang, Ruifang; Cui, Yongwei (International Journal of Agricultural and Biological Engineering, 2025)
Soil physicochemical properties, climate, and human activities can create barriers to arable land in varying degrees, affecting land quality. The Huanghuaihai Plain (HHHP) is an important agricultural region in China. To clarify the factors influencing the formation of barriers to arable land in this area and their spatial distribution characteristics, this study took the northern part of the HHHP as the research object, screened and quantified the factors influencing barriers to arable land, constructed a multifactor-based arable land barrier evaluation index system, and used the index system to spatially classify the barriers to arable land. The results showed that 1) 16 evaluation indicators including the five dimensions of chemical indicators, physical indicators, biological indicators, management measures, and plot environment were screened out through the random forest model; 2) the average rating of the multifactor barrier for arable land in the northern part of the HHHP was 5.3, exhibiting a medium level, and the area of grade 5 and grade 6 land accounted for the highest percentage, at up to 30%; 3) the order of barrier degree of main barrier factors from high to low was organic matter>salt content>available phosphorus>available potassium>irrigation capacity>soil texture class>soil bulk density; and 4) according to the idea of ranking barrier factors, 15 types of barriers were obtained and then divided into the three major barrier area categories of organic matter, irrigation capacity, and salinity, and the prioritization of cropland quality improvement was determined according to the sequential order of the combination of barrier factors. A preliminary multifactor barrier index system for croplands was constructed, which can provide a reference for cropland barrier abatement and the precise improvement of cropland quality in the HHHP area. Key words: Huanghuaihai Plain; cultivated land; barrier factors; evaluation system; barrier types DOI: 10.25165/j.ijabe.20251802.9428 Citation: Guo X Y, Zhang C, Liu Z H, Yin B Z, Wang H, Li X G, et al. Construction of a multifactor barrier evaluation system and classification of barrier types for arable land on the northern Huang-Huai-Hai Plain. Int J Agric & Biol Eng, 2025; 18(2): 189–196.